Three new species of the funnel-web spider genus Macrothele from the Southwest China (Mygalomorphae: Macrothelidae) - Tang, Ya-Ni; Zhao, Yu; Yang, Zi-Zhong (Zootaxa, 2020)
Three new species of the genus Macrothele are described from Yunnan Province, China: Macrothele undata sp. nov., M. arcuata sp. nov., M. sanheensis sp. nov. Detailed morphological descriptions of the three new species are provided.